FUNDAMENTALIZATION OF EDUCATION IN THE CONTEXT OF FORMATION OF THE KNOWLEDGE SOCIETY AND SOCIAL SECURITY - Kutsenko, Vira; stavnycha, nataliia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article examines the role of fundamental education in ensuring the development of the economy on an innovative basis and in achieving social security. The content of the fundamentalization of education has been investigated. At the same time, both theoretical and practical prerequisites for its achievement are indicated. The main ways of achieving fundamental education are determined, and its main components are analyzed, namely: motivational, cognitive, activity, etc. Accordingly, it is proved that the fundamentalization of knowledge accelerates the formation of an innovative economy and a knowledge society, which are modern models of socio-economic development. An assessment of the current situation regarding the quality of education, which is now provided by the educational system of Ukraine, is given and a conclusion is made about its insufficiently high level. In this regard, the need to fill the educational process with an innovative essence is emphasized, which includes both the introduction of the latest electronic digital technologies and innovative educational and pedagogical approaches. On the one hand, the article also substantiates the provision that social safety, on the other hand, is a consequence of the development of education, and on the other - it contributes to the latter. In this context, the article provides the criteria and characteristics of a safe educational environment, the need for the formation of which is also noted in the National Strategy for the Development of Education in Ukraine. It is emphasized that the main condition for maintaining social safety is successful economic development. An important place in the article is occupied by the substantiation of the directions in which the educational sphere should develop. Among these areas, the active introduction of social and pedagogical partnership stands out, which is an effective form of interaction between all participants in the educational process. All this is designed to contribute to the formation of an innovative economy and a knowledge society, and the achievement of social safety.